Audit Publicity and Tax Compliance: A Natural Experiment. (11th July 2019) - Battiston, Pietro; Duncan, Denvil; Gamba, Simona; Santoro, Alessandro
Abstract: We use confidential data on value‐added tax payments at the sector level, in two large Italian cities, to estimate the effect of audit publicity on the tax compliance of local sellers. By employing a difference‐in‐differences identification strategy, we find that such publicity has a positive effect on fiscal declarations made shortly thereafter. The results suggest that increasing awareness on future audits via the media can be an important instrument in the hands of tax authorities.